2017
DOI: 10.1371/journal.pone.0182943
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among single and partnered parents in South Korea

Abstract: ObjectiveThis study compares the mental health of single parents relative to partnered parents and assesses the contribution of the social and demographic factors to this difference, examining the gender difference in it.MethodsWe analyzed 12,024 single and partnered subjects, aged 30–59 years, living with children, aged 0–19 years, drawn from the 4th, 5th, and 6th Korea National Health and Nutrition Examination Survey (KNHANES) dataset in South Korea conducted from 2007–2013. Mental health was evaluated by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 34 publications
1
40
1
Order By: Relevance
“…South Korea is a highly competitive society that has experienced rapid economic and sociocultural changes over the past few decades. The costs of these rapid changes include occupational stress, rising housing prices, and high divorce rates, all of which are closely associated with depression in South Korea 38 40 . We compared the prevalence of three different categories of depression, i.e., Dx, Dx and Mx, and Dx or Mx, and the overall trends were similar.…”
Section: Discussionmentioning
confidence: 99%
“…South Korea is a highly competitive society that has experienced rapid economic and sociocultural changes over the past few decades. The costs of these rapid changes include occupational stress, rising housing prices, and high divorce rates, all of which are closely associated with depression in South Korea 38 40 . We compared the prevalence of three different categories of depression, i.e., Dx, Dx and Mx, and Dx or Mx, and the overall trends were similar.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that parental psychosocial stress increases the risk of their children developing asthma and allergic diseases [21][22][23][24][25]. An association between single-parenthood and increased parental psychosocial stress has also been reported [26][27][28][29]. Mullins et al identi ed an association between being a single parent and peoples' parenting capacities, suggesting that children living in single-parent households may not receive enough care, resulting in their increased morbidity of chronic health conditions [26].…”
Section: Discussionmentioning
confidence: 99%
“…A study of Korea found that the greater risk of poor mental health among single mothers is often explained by low socioeconomic status, social support and stress. Single parents, especially single mothers, were reported to have poor health, especially mental health, higher risk of early death, more feeling of weakness and poor self-perceived health than partnered parents (Kong et al, 2017). Single motherhood is also associated with lower age and education.…”
Section: Discussionmentioning
confidence: 99%
“…Coping with childrearing for single parents becomes more difficult because of responsibility overload, task overload, and emotional overload. Alone or in combination, these result in problems for the single parent, including loneliness, anxiety and depression (Kim et al, 2018; Kong et al, 2017; Rousou et al, 2019; Subramaniam et al, 2014; Theodoritsi et al, 2018). Nevertheless, they have increased mortality risk may be due to strain and consequences of the stress of lone motherhood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation